1995
DOI: 10.1016/0029-7844(94)00434-f
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in women with uterovaginal prolapse and urinary incontinence

Abstract: Women with prolapse and urinary incontinence do not differ from continent women without prolapse in measures of sexual function; age is the most important predictor of sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 10 publications
8
93
2
2
Order By: Relevance
“…These are consistent with prior research (14)(15)(16). However, in contrast to other studies (16), these characteristics did not confound the association between pelvic floor symptoms and sexual function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These are consistent with prior research (14)(15)(16). However, in contrast to other studies (16), these characteristics did not confound the association between pelvic floor symptoms and sexual function.…”
Section: Discussionsupporting
confidence: 91%
“…This provided an opportunity to assess the impact of pelvic floor disorders across a spectrum of symptoms and severity. Prior research has been limited either to community samples (4) or women seeking gynecologic care (2,3,16,17). In community samples, the women who report pelvic floor disorders are likely to have relatively mild symptoms and therefore the impact on sexual function might therefore be minimal in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence has also been implicated to have an adverse effect on female sexuality. [3][4][5][6][7][8] Temml et al 4 reported that 25.1% of women with urinary incontinence had sexual impairment to some degree. Psychological distress, fear of incontinence during intercourse, embarrassment due to odor been suggested in the etiology sexual dysfunction.…”
Section: 2mentioning
confidence: 99%
“…Some suggest that sexual function is adversely affected by pelvic floor dysfunction, [16][17][18] whereas others advocate the opposite. 19,20 The aim of this case-control study was to assess the risk of sexual dysfunction in obese women in relation to lower urinary tract symptoms in an obese population sample with a body mass index (BMI) X30 kg/m 2 compared to nonobese women with BMI o30 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%